ANALISIS ALIH KODE DALAM LAGU "CASABLANCA" - Basit, Abdul; Nandang, Ade; Hidayah, Vina (Widyaparwa, 2024)
The reason for this research is so that the song “Casblanca” is not only enjoyed as a song but can be enjoyed as intellectual property. The aim of this research is to reveal the lyrics, types and functions of code switching in the song “Casbalanca”. Code switching is a symptom of language transition and is a substudy of sociolinguistics. The types of code switching include; internal, and external. In this research, a qualitative descriptive method was used with content analysis techniques consisting of 3 stages, namely providing, analyzing and presenting code switching data on the lyrics of the song “Casablanca”. This research produces an interpretation of the data obtained in the form of transcriptions of song lyrics. The type of code switching in the song Casablanca is external code switching. The code switching analysis is in the form of the lyrics of the song Casablanca which tells about someone who wants to live forever with the person he loves and loves and hopes that separation will never happen forever and the code switching function analysis is in the form of 1) referential, 2) conative, 3) emotive, 4) poetic, 5) phatic and 6) metalinguistic. This research has implications for increasing the sociolinguistic scientific knowledge of the sub-study of external code switching, especially in the lyrics of the song Casablanca.Alasan penelitian ini ialah agar lagu “Casblanca” tidak hanya dinikmati sebagai lagu saja melainkan bisa dinikmati sebagai kekayaan intelektual. Tujuan penelitian ini yaitu mengungkap lirik, jenis dan fungsi alih kode pada lagu “Casbalanca”. Alih kode yaitu gejala peralihan bahasa dan merupakan subkajian sosiolinguistik. Adapun jenis alih kode di antaranya ialah intern dan ekstern. Pada penelitian ini digunakan metode deskriptif kualitatif dengan teknik analisis isi yang terdiri atas 3 tahap, yakni penyediaan, analisis, dan penyajian data alih kode pada lirik lagu “Casablanca”. Penelitian ini menghasilkan interpretasi terhadap data yang diperoleh berupa transkripsi lirik lagu. Jenis alih kode pada lagu “Casablanca” yaitu alih kode ekstern. Adapun analisis alih kode berupa lirik lagu “Casablanca” yang menceritakan tentang seseorang yang ingin hidup selama-lamanya bersama orang yang dia cintai dan dia kasihi serta berharap perpisahan takkan pernah terjadi sampai kapanpun. Analisis fungsi alih kodenya berupa 1) referensial, 2) konatif, 3) emotif, 4) puitis, 5) fatis, dan 6) metalinguistik. Penelitian ini berimplikasi terhadap bertambahnya khazanah keilmuan sosiolinguistik subkajian alih kode ekstern khususnya dalam lirik lagu “Casablanca”.